Analysis of the Physical Properties of Laikang II Reservoir Water in Takalar Regency as an Alternative for Clean Water - Sulistiawaty, Sulistiawaty (Jurnal Biologi Tropis, 2026)
Reservoirs are essential water resources that function to store rainwater runoff, support irrigation activities, and maintain water availability during dry seasons. This study aimed to analyze the water quality of Laikang II Reservoir, Takalar Regency, based on physical water quality parameters. A quantitative descriptive approach was employed with water sampling at three locations: Well 1 (S1), the reservoir (S2), and Well 2 (S3). The analyzed parameters included temperature, Total Dissolved Solids (TDS), turbidity, color, odor, taste, and pH. The results were evaluated by comparing them with Government Regulation No. 22 of 2021 (Class II water quality standards) and Minister of Health Regulation No. 2 of 2023 concerning hygiene and sanitation requirements. The results showed that most physical water quality parameters in Laikang II Reservoir generally met the Class II water quality standards. However, turbidity and color in S2 (reservoir water) exceeded the permissible limits for hygiene and sanitation purposes, indicating localized water quality degradation. In contrast, S1 and S3 showed relatively better water quality conditions, suggesting that groundwater sources are less affected by surface contamination compared to the reservoir. These findings highlight that reservoir water quality is more vulnerable to environmental pressure, particularly from sedimentation and surrounding land-use activities. Therefore, continuous water quality monitoring, control of domestic and agricultural runoff, implementation of buffer vegetation zones, and sediment management are recommended to maintain the sustainability of the reservoir as a water resource.